Lemierre’s disease: a typical presentation in two diabetic patients - Kalbani, Bushra Hamdan Al; Singh, Amar; Sheibani, Salma Mohd Al (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Lemierre disease (LD) is a rare but potentially life-threatening condition, characterized internal jugular vein suppurative thrombophlebitis and disseminated septic emboli following a recent oropharyngeal infection. It is seen commonly in healthy young adolescents or adults, caused by gram negative anerobic Fusoform necropharum. Lack of awareness of this condition delays treatment and worsens prognosis. We present two interesting cases of LD in diabetic patients, caused by Klebsiella pneumonia and Haemophilus influenza organisms at our hospital. Both patients had atypical presentations. Diagnosis of such atypical cases poses diagnostic and therapeutic challenges.